Carbon Ion Therapy: A Modern Review of an Emerging Technology - Malouff, Timothy D.; Mahajan, Anita; Krishnan, Sunil; Beltran, Chris; Seneviratne, Danushka S.; Trifiletti, Daniel Michael (Frontiers in Oncology, 2020)
Radiation therapy is one of the most widely used therapies for malignancies. The therapeutic use of heavy ions, such as carbon, has gained significant interest due to advantageous physical and radiobiologic properties compared to photon based therapy. By taking advantage of these unique properties, carbon ion radiotherapy may allow dose escalation to tumors while reducing radiation dose to adjacent normal tissues. There are currently 13 centers treating with carbon ion radiotherapy, with many of these centers publishing promising safety and efficacy data from the first cohorts of patients treated. To date, carbon ion radiotherapy has been studied for almost every type of malignancy, including intracranial malignancies, head and neck malignancies, primary and metastatic lung cancers, tumors of the gastrointestinal tract, prostate and genitourinary cancers, sarcomas, cutaneous malignancies, breast cancer, gynecologic malignancies, and pediatric cancers. Additionally, carbon ion radiotherapy has been studied extensively in the setting of recurrent disease. We aim to provide a comprehensive review of the studies of each of these disease sites, with a focus on the current trials using carbon ion radiotherapy.